2021
DOI: 10.33448/rsd-v10i14.22174
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da influência do estágio de lactação na concentração dos principais ácidos graxos de lactante com bebê nascido a termo

Abstract: O presente estudo tem como objetivo avaliar a influência dos estágios de lactação (colostro, transição e maduro) na composição dos principais ácidos graxos e somatórios de ácidos graxos no leite humano de lactante com bebê nascido a termo. Para isso foi coletado de forma individualizada, no mesmo período do dia, e após 1 hora da mama ser esvaziada, por meio de ordenha manual cerca de 5 ml de leite humano, em seguida foi realizada a composição de ácidos graxos por meio de cromatografia em fase gasosa acoplado a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
2
0
2
Order By: Relevance
“…de la Garza Puentes et al (2019) showed that breast milk of mothers with a high BMI presented decreased ALA and DHA concentrations than milk from normal weight nursing mothers. This finding corroborates what was observed in our study, when comparing the levels of ARA and DHA found in the BM samples of the nursing mother studied with that of Castro et al (2021), who used COL, TM and MM samples from eutrophic women. It is important to point out that the nursing mother in the study was still in weight loss due to performing the BS only two months before the beginning of the pregnancy and presenting a nutritional diagnosis of overweight.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…de la Garza Puentes et al (2019) showed that breast milk of mothers with a high BMI presented decreased ALA and DHA concentrations than milk from normal weight nursing mothers. This finding corroborates what was observed in our study, when comparing the levels of ARA and DHA found in the BM samples of the nursing mother studied with that of Castro et al (2021), who used COL, TM and MM samples from eutrophic women. It is important to point out that the nursing mother in the study was still in weight loss due to performing the BS only two months before the beginning of the pregnancy and presenting a nutritional diagnosis of overweight.…”
Section: Resultssupporting
confidence: 92%
“…Berenhauser et al (2012) also found higher ALA value in the MM: 0.86%. Castro et al (2021), investigating the LNA content in BM, found in COL: 26.52%, TM: 22.34% and 22.26% in MM and ALA in COL: 1.71%, TM: 1 .12% and 1.57% in the MM, values much higher than those in our case report. This difference in results suggests that malabsorption of these lipids may have occurred, since BC significantly alters the dynamics of the digestive process.…”
Section: Resultscontrasting
confidence: 82%
See 2 more Smart Citations